Cross-national differences in income poverty among Europes 50+ - Daniel Hallberg (Uppsala University, Department of Economics, 2006)
This paper studies income poverty among the 50+ population in 10 EU countries using newly collected data from the SHARE (Survey of Health, Ageing and Retirement in Europe) project. A measure of the households disposable annual income is used. Relative income poverty range from 10 percent (in Sweden) to 22 percent (in Switzerland). Logistic regression estimates show that unemployment, being a homemaker, self-employed, living single, and having a child living close, are associated with an increased likelihood of poverty. Less risk of poverty can be found among those that have supervision over the workplace, have obtained more education, are home owners, and, in some countries, among those that are relatively old.
urn:nbn:se:uu:diva-83089
Keywords: D31; I31; I32; J14; 330; Poverty; disposable income; household income; cross-country comparison; relative poverty; Einkommensverteilung; Haushaltseinkommen; Armut; Niedrigeinkommen; Alte Menschen; Vergleich; EU-Staaten